Klein–Gordon–Maxwell Systems with Nonconstant Coupling Coefficient - Lazzo Monica; Pisani Lorenzo (Advanced Nonlinear Studies, 2018)
We study a Klein–Gordon–Maxwell system in a bounded spatial domain under Neumann boundary conditions on the electric potential. We allow a nonconstant coupling coefficient. For sufficiently small data, we find infinitely many static solutions.